A System Model of Fault Tolerance Technique in the Distributed and Scalable System: A Review (International Journal of Innovative Research in Computer Science & Technology, 2022)
Fault tolerance is one of the most crucial  concerns in distributed systems. Flout tolerance system is  very difficult to implement due to its dynamic nature and  complex services. Several research efforts consare istently  being made to implement that tolerance in a distributed  system. Some recent surveys try to incorporate the several  fault tolerance architectures and methodologies proposed for  a distributed system. This paper gives a systematic and  comprehensive interpretation of different fault types, their  causes, and various fault-tolerance approaches used in a  distributed system. The paper presents a broad survey of  various fault tolerance frameworks in the context of their  basic approaches, fault applicability, and other key features.  we investigate the different techniques of fault tolerance  which is used in a distributed and scalable system. Scalability  is an important factor in distributed Systems. It describes the  ability of the system to dynamically adjust its own computing  performance by changing available computing resources and  scheduling methods. The focus of this paper is on types of  faults occurring in the system and fault detection techniques.  A fault can occur in the system due to the link failure or for any other reason. An appropriate fault detection technique  can avoid a loss and save from system failure. The main  objective of the fault-tolerant computer system is to continue  operating uninterrupted despite the failure of one or more of  its components. In the early day’s computer systems were not  distributed and they also did not share resources. Now, most  of the computers are distributed. They work independently  on a common task. So, if one system gets any fault then the  other systems will take over the computation of the fault  system. The user will not get any issues with his tasks.
Keywords: Load balancing; Fault tolerance system; Server authentication